Canopy Near-infrared Observation Project - Shuldes, Garrett Michael (Proceedings of the Wisconsin Space Conference, 2020)
The Canopy Near-infrared Observing Project (CaNOP) will utilize a multispectral pushbroom imager in a 3U CubeSat to carry out spectrally resolved imaging of global forest regions with spectral resolution sufficient to reproduce the LandSat 8 mission and calculate vegetation indices. The project provides an educational experience for undergraduate students to design, build, test, and operate a 3U CubeSat. Using concepts from fields such as physics, engineering, and computer science, students were to link the electrical, mechanical, and software components of the satellite together to create a flawless flow of information and power across the entirety of the satellite and its corresponding ground stations to which the images of the global forest regions will be transferred and analyzed. Two vegetation indices; the Normalized Difference Vegetation Index (NDVI) and the Enhanced Vegetation Index (EVI) will be used in combination with the Net Primary Production (NPP) of any forest to produce the Gross Primary Production (GPP), which will then provide the information required to answer the argument that the CaNOP team’s hypothesis proposes: An old-growth forest will absorb more carbon than a newly grown secondary forest.